Respostas subjetivas relacionadas à ingestão alimentar e estado de ansiedade após noites de trabalho versus noites de sono - Silva, Ane Andrade Santa Cecília (2016)
Subjective responses to meals, like hunger, enjoyment and satiety, are altered by the shortening of sleep time, but this effect is poorly studied in shift workers – a typical model of sleep restriction. Objectives: The aim of this prospective and observational study was to compare the subjective perceptions to meals and the level of anxiety after working nights shift versus nights of regular sleep, and investigated the associations between the responses to meals and the levels of anxiety under these two conditions. Methods: The study evaluated 34 male night shift workers who worked a 12- hour shift followed by a 36-hour rest period. Evaluations included hunger, enjoyment of eating foods and satiety to all meals, which were evaluated with a visual analogue scales in three non-consecutive days after working night shift and three non-consecutive days after regular sleep; state of anxiety (in a day after working night shift and a day after regular sleep); and sleep pattern (in three days after working night shift and three days after regular sleep). Data referring to the days that followed night shift work and nights of regular sleep were grouped together and compared. Linear regression were used to indicate associations between hunger and anxiety. Results: In the days following a worked night shift, workers presented higher mean hunger scores before lunch and higher anxiety scores than for the day after nights of regular sleep (p=0.007 and 0.001, respectively). Linear regression indicate that after a worked night shift, anxiety scores were negatively associated with hunger before breakfast (β= -0.44, p = 0.04, R² = 0.18) and lunch (β= -0.35, p = 0.03, R² = 0.19); enjoyment of eating foods (β= -0.34, p = 0.03, R² = 0.22) and quantity of meals throughout the day (β= -0.37, p = 0.03, R² = 0.21), which did not occur to the same magnitude after a night of regular sleep. Conclusion: Night shift increases the mean hunger and anxiety scores and seems to interfere with the responses associated with food consumption, which may in part justify the alterations in food intake pattern regularly observed in these workers.